Apropiación privada de la tierra y derechos políticos en la obra de John Locke - Severo Chumbita, Joan (Ingenium. Revista Internacional de Pensamiento Moderno y Metodología en Historia de las Ideas, 2014)
In order to consider the influence of tangible property on the exercise of political rights in the work of John Locke, we’ll analyze, first, the distribution and acreage measurement of the requirements for political participation and the exercise of public functions in The Fundamental Constitutions of Carolina; secondly, the considerations on land ownership, as a means of production, and the wage labor in Chapter V of Two Treatises of Government, II; finally, we’ll analyze the patrimonial restrictions for the access to political rights, as well as the suggested participation for workers in Some Considerations of the Lowering of Interest, and Raising the Value of Money.
Keywords: Locke; appropriation; land; political rights